Differential alcohol treatment response by gender following use of VetChange. (1st April 2021) - Livingston, Nicholas A.; Simpson, Tracy; Lehavot, Keren; Ameral, Victoria; Brief, Deborah J.; Enggasser, Justin; Litwack, Scott; Helmuth, Eric; Roy, Monica; Rosenbloom, David; Keane, Terence M.
Highlights: Proportionally more veteran women than men registered to use VetChange. Veteran men and women evidenced similar rates of intervention use over six months. Veteran men and women reported similar reductions in posttraumatic stress over time. Veteran women did not decrease their drinking as much as veteran men. Abstract: Objective: Proportionally more women use online alcohol interventions but also report less robust treatment outcomes compared to men. Less is known about outcome disparities among veteran women, who are a growing demographic nationally. The current study examined gender differences among returning veteran men and women who used VetChange, a web-based intervention for hazardous drinking and posttraumatic stress symptoms (PTSS). Method: Using data from a nationwide implementation study of returning combat veterans ( n = 222), we performed hierarchical linear modeling to examine gender differences in alcohol and PTSS outcomes over six months following VetChange registration. Additional analyses examined gender differences in proportional changes in hazardous drinking and at each assessment point. Results: Returning veterans reported significant decreases in alcohol use and PTSS over time, yet men evidenced significantly greater reduction in average weekly drinks and drinks per drinking day compared to women. Follow up analyses indicated that women were significantly less likely than men to achieve low-risk drinking by one month post-registration. Proportional change in alcohol use yielded marginal and non-significant trends that were, nonetheless, consistent with the overall pattern of gender differences. Conclusion: These results contribute to emerging literature suggesting that women use online alcohol use interventions at proportionately higher rates than do men, but do not reduce their drinking as much as men. There are a number of potential content changes that could improve outcomes for returning veteran women using online interventions, and data-driven adaptations based on stakeholder input are recommended.